If I Cannot See It, It Is Not There - A Graphical Approach to De-escalating Commitment - Michels, Leonard (SIGMIS-CPR'20: Proceedings of the 2020 on Computers and People Research Conference, 2020)
Escalation of commitment is a common bias in human decision- making. It has been studied for more than 40 years, however, an effective measure to de-escalate commitment is still missing. In order to find a new method of de-escalating commitment, this paper integrates past research on the effects of information about opportunity costs on escalation of commitment, and on the influence of information systems using graphical presentation formats on human decision making. It investigates whether graphically presenting information about opportunity costs or sunk costs influences an individual's tendency to escalate commitment. An online experiment with 380 participants was conducted, in which four decision scenarios were presented. The participants received information about the decision alternatives either in a table or in dashboards containing one graph and a table. Contrary to the first hypothesis, graphically presenting information about opportunity costs did not lead to decreased escalation behavior. The second hypothesis, which proposed an increasing effect of graphically presenting information about sunk costs, was supported by the data. Information systems using graphical information presentation might, therefore, be a promising approach to alter human decisions in economic contexts.<br
Keywords: Decision support; escalation of commitment; visualization